Improve the energy efficiency of a full scale integated fixed film activated sludge (IFAS) process at Thames Water Oxford WWTW - Buñol i Tordera, Ramon (Cranfield University, 2009)
The primary objective of integrated fixed film activated sludge (IFAS) is to remove dissolved pollutants from wastewater. This process allows an increased treatment capacity in comparison with conventional activated sludge. Thames Water has been operating a full scale IFAS biological process demonstration lane of 870 m 3 at the Oxford wastewater treatment works for over two years. The aim of this study was to evaluate the benefits of using an ammonia feed back control system as an alternative to a conventional set point dissolved oxygen control in order to improve energy efficiency in the aeration system. The main finding was that the adjustment of dissolved oxygen (DO) set points regulated by the feedback control system resulted in periods of excess or deficiency of DO in the wastewater with an total over aeration of 14.7 % and under aeration of 9.8 %. Investigation into the causes of the deviations found that the speed of the control equipment was unable to match the responsiveness of the control set point leading to periods where the air control valve was either too open or too closed. A linear equation was established to relate the influent wastewater flow with the time taken by the ammonia to be detected in the settled sewage stream in the IFAS process lane. Thus a feed forward control philosophy was suggested to control the aeration system, as opposed to the feed-back control system in order, to improve the target DO set point. Alongside this study, a comparison of the energy costs between IFAS with the ammonia feed-back control philosophy and a conventional activated sludge set point DO control system was completed. The analysis found negligible difference between the two processes. In addition when compared to the calculated design aeration requirements for set point DO control for the observed actual oxygen required (AOR) loadings, it was found that operating the IFAS system in NH4-N feed back control requires significantly less air. It can therefore be concluded that, with further research, the IFAS process can still be optimised to reduce aeration energy costs.
Keywords: activated sludge; dissolved pollutants; ammonia feed back control system; dissolved oxygen; energy costs; actual oxygen required